APPLICATION OF FUZZY EXPANSION METHODS FOR SOLVING FUZZY FREDHOLM- VOLTERRA INTEGRAL EQUATIONS OF THE FIRST KIND - Fallah Jelodar, Sh. S.; Allahviranloo, T.; Abbasbandy, S. (International Journal of Mathematical Modelling & Computations, 2013)
In this paper we intend to offer new numerical methods to solvethe fuzzy Fredholm- Volterra integral equations of the firstkind $(FVFIE-1)$. Some examples are investigated to verify convergence results and to illustrate the efficiently of the methods.